2017
DOI: 10.1111/cch.12446
|View full text |Cite
|
Sign up to set email alerts
|

Time use of parents raising children with severe or profound intellectual and multiple disabilities

Abstract: This study shows that the parents of children with PIMD have to spend a significant amount of time on care tasks and have on average 1.5 h less free time per day than parents of typically developing children. This is a striking difference, because leisure time can substantially contribute to well-being. Therefore, it is important not only to consider a child with PIMD's support needs but also to identify what parents need to continue their children's daily care and supervision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
47
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 24 publications
3
47
0
1
Order By: Relevance
“…This last negative impact corresponds with a study by Dobson and Middleton (1998), who found that the costs of raising a child with severe disabilities are three times as high as those of raising a typically developing child. Parents' negative appraisal of the extraordinary demands on their time corresponds with previous research showing that parents spend significantly more time on care tasks compared to parents raising typically developing children (Luijkx et al, 2017). Their free time, on the other hand, was substantially limited compared to parents raising typically developing children.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…This last negative impact corresponds with a study by Dobson and Middleton (1998), who found that the costs of raising a child with severe disabilities are three times as high as those of raising a typically developing child. Parents' negative appraisal of the extraordinary demands on their time corresponds with previous research showing that parents spend significantly more time on care tasks compared to parents raising typically developing children (Luijkx et al, 2017). Their free time, on the other hand, was substantially limited compared to parents raising typically developing children.…”
Section: Discussionsupporting
confidence: 74%
“…Positive appraisals may be important in helping parents continue their care tasks over a long period (Folkman & Moskowitz, 2000), especially in parents of children with PIMD. Their substantial negative appraisal of the impact on family life combined with the extreme time burden (Luijkx et al, 2017) calls for support tailored to the needs and wishes of families with children with PIMD and to promote optimal family quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite being supported by human and technical assistance, the burden on families is likely to be considerable. Some studies have explored burden on informal caregivers who have children with multiple disabilities7–9 and in informal caregivers who have children with cerebral palsy 10–14. The caregivers reported deteriorated health status, financial difficulties, restriction in their social participation and physical overload.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of the significant motor and cognitive limitations provides the child as well as the parent with specific challenges, because of the dynamic influences between these and other developmental domains (Fagnart, ; McCollum, ) as well as additional practical and emotional barriers. For example, parents need to invest a lot of time in physical care tasks and support activities for their child with multiple and complex needs and may still be in the acceptance process, potentially disrupting the otherwise natural and spontaneous course of everyday activity (Brett, ; Luijkx, van der Putten, & Vlaskamp, ; Tadema & Vlaskamp, ). Also, there is a great need for people in the child's proximal environment to act as “scene‐setters,” that is to arrange opportunities for child participation (Axelsson, Imms, & Wilder, ).…”
Section: Introductionmentioning
confidence: 99%